Protection performance of Azadirachta indica leaf essential oil on corrosion of plain carbon steel in weak HCl and NH4Cl - Tolulope Loto Roland; Akpanyung Kingsley (E3S Web of Conferences)
Azadirachta indica leaf essential oil (ADI) was assessed for its corrosion protection properties on plain carbon steel within 0.5 M HCl, 3.74 M NH4Cl, 1 M HCl, and 5.61 M NH4Cl. Weight loss data indicates ADI exhibited strong inhibition properties in HCl, with peak performance of 97.53% and 97.55% at 5% ADI. The results indicates strong molecular interaction between protonated ADI molecules and the charged steel surface. ADI showed poor inhibition at 1-4% ADI within NH4Cl, at values below 50%. At 5% ADI concentration, the data considerably rose to 78.52% and 78.0% after 312 h. This shows ADI performance in NH4C is significantly concentration dependent which limits it versatility compared to its performance in HCl solution. Standard error for ADI performance within 0.5 M HCl were extreme, suggesting thermodynamic stability of inhibitor molecules. Standard error were lower in 1 M HCl, 3.74 M NH4Cl, and 5.61 M NH4Cl. Numerical data showed a portion of ADI protection performance values generally exceeded 70%. Statistical analysis showed immersion duration was more dominant on the performance of ADI compared to ADI concentration, while ADI concentration wasmore influential in NH4Cl.